Modern Technologies For Sustainable Agriculture - Kumar, Sunil (New Delhi : New India Publishing Agency (NIPA), 2021)
Application of biotechnology in Hi-tech agriculture/Atul Kumar and Vandana A. Kumar. 2. Crop selection an efficient tool for sustainable agricultural production in the impending climate change situation/Anil Kumar Singh, U.R. Sangle and Pravesh Kumar. 3. Management of soil fertility for sustainable vegetable production/Sobaran Singh, S.K. Maurya and Poonam Gangola. 4. Microbial inoculation through endophytic bacteria for sustainable agriculture/K. Swarnalakshmi, M. Senthikumar and Sanjay Sachan. 5. Seed enhancement technologies for assured plant stand establishment/S.K. Yadav, Arun Kumar M.B.
0 -- 1 -- 2 -- 3 -- 4 -- 5 -- 6 -- 7 -- 8 -- 9 -- 10 -- 11 -- 12 -- 13 -- 14 -- 15 -- 16 -- 17 -- 18 -- 19 -- 20 -- 21 -- 22
Description based upon print version of record.
Added to collection customer.56279.3
Keywords: Sustainable agriculture -- India; Agricultural innovations -- India; Electronic books